Classification and pragmatic linguistic characteristics of the short vertical video genre in German-speaking educational discourse - M. A. Goncharova (Вестник Самарского университета: История, педагогика, филология)
The article considers a new video format that has become extremely popular due to its perfect alignment with mosaic thinking. Although these videos are widely spread on social media, they remain understudied from a linguistic perspective. Despite their recent appearance, short vertical videos within the modern educational discourse exhibit characteristics of an established genre, showcasing users’ creativity and their ability to adapt the format for educational purposes. The author identifies genre-defining (formal) and genre-forming (functional) parameters of VK Clips and proposes their classification. According to specific communicative goals, the article distinguishes between entertainment-educational, expert (methodological, cultural, linguistic), and presentation-educational (featuring language material and speech situations) short vertical videos. The author views the subgenres of VK Clips both multimodal texts and analyzing their features through the lens of various semiotic codes and information transmission channels, employing the method of discourse analysis, and elements of the multimodal transcription method by A. Baldry and P. Thibault, and the comprehensive polysemiotic approach by Y. Gambier. Entertainment-educational videos serve an advertising function. They are few in number and lack common characteristic features, aside from formal ones. The expert videos focus on the blogger as the central figure, whose role is to hold the audience’s attention through the message and their public speaking skills. Special emphasis is placed on verbal linguistic and non-verbal paralinguistic codes, while other codes are used minimally. In contrast, presentation-educational VK Clips actively use a variety of codes and modalities, but the material is presented without in-depth explanation.